CAMPATH-1 monoclonal antibody therapy in severe refractory autoimmune thrombocytopenic purpura. - Lim, S; Hale, G; Marcus, R; Waldmann, H; Baglin, T (1993)
Six patients with autoimmune thrombocytopenic purpura (three of whom had CLL/NHL and one previous Hodgkin's disease) refractory to conventional therapy were treated with an antilymphocyte monoclonal antibody directed at CDw52 (CAMPATH-1). We observed response in four of the five evaluable patients; in three patients the response has lasted more than 4-9 months. However, response did not occur in most cases until 4-6 weeks after the commencement of the antibody therapy, suggesting that the mechanism of action is probably that of immune modulation.